INDIKATOR YANG MEMPENGARUHI DINAMIKA CADANGAN DEVISA DI INDONESIA SEBELUM DAN SESUDAH ADANYA KRISIS GLOBAL - Mita Pratiwi; Rifki Khoirudin (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2022)
This research aims to analyze the influence of exports, imports, exchange rates, inflation, foreign debt on Indonesia's foreign exchange reserves. This study uses time series data in 2000-2020 (monthly) obtained from Bank Indonesia and the Central Statistics Agency. In this study researchers used multiple linear regression methods with the help of E-Views9 software. The results showed partial exports, exchange rates, inflation and foreign debt had a significant effect on foreign exchange reserves. Based on the results obtained, it can be explained that exports have a significant positive effect on foreign exchange reserves, exchange rates have a significant negative effect on foreign exchange reserves, inflation has a significant negative effect on foreign exchange reserves, and foreign debt has a significant positive effect on foreign exchange reserves. As for import variables, negatively insignificant influence on foreign exchange reserves. In addition, simultaneously the overall variable affects 98.5071% of foreign exchange reserves, while the rest is influenced by other variables outside of the variables used.